Any Port(ico) in a Storm. Field Notes on an Adult Amateur Synagogue Choir during the Pandemic - Shansky, Carol (Revue musicale OICRM, 2022)
This set of field notes relates the experiences of an adult amateur synagogue choir during the two years of the covid-19 pandemic. The director’s observations comprise the notes and reflections on the meaning of music in the lives of the choir members, the challenges faced by the ensemble to continue rehearsing despite the shutdown, and the different ways that those challenges were met.